Experimental and Theoretical Studies on Corvol Ether Biosynthesis. Issue 2 (4th December 2015) - Rabe, Patrick; Janusko, Aron; Goldfuss, Bernd; Dickschat, Jeroen S.
Abstract: The biosynthesis of corvol ethers A and B, two sesquiterpenes from Kitasatospora setae, proceeds with involvement of either one 1, 3‐ or two sequential 1, 2‐hydride shifts. Quantum chemical calculations revealed that the sequence of two 1, 2‐hydride shifts is energetically favoured. Labelling experiments were in agreement with this finding. In addition, the stereochemical course of a reprotonation step was investigated by incubation of 13 C‐labelled isotopomers of farnesyl diphosphate in water and in deuterium oxide. Abstract : Internal hydride migrations during corvol ether biosynthesis were investigated. Quantum chemical calculations revealed a sequence of two 1, 2‐hydride shifts to be energetically favoured; labelling experiments were in agreement with this. In addition, the stereochemical course of a reprotonation step was investigated with 13 C‐labelled isotopomers of farnesyl diphosphate in water and in deuterium oxide.